DESENVOLVIMENTO DE UM BANCO DE DADOS CONTENDO ESTRATÉGIAS DE PROJETO DE EDIFÍCIOS DE ESCRITÓRIOS DE MODO MISTO - Pereira, Fernanda; Neves, Leticia (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The mixed-mode system recently appeared in academic researches as a prominent strategy to reduce energy consumption in office buildings. This strategy, associated with envelope design optimization, can present satisfactory results in relation to indoor environmental conditions, reduction of energy consumption and operation costs with the air-conditioning system. However, a first literature review showed discrepancies between the expected and the real design of mixed-mode office buildings, in particular to circumstances. Therefore, investigations considering data generated from field surveys in real buildings become necessary. The present study develops a database containing information collected through a field survey about mixed-mode office buildings located in the city of Sao Paulo, a Brazilian humid subtropical climate location. The method is organized in three sections: sample selection of buildings for field survey; field data collection; statistical analyses and analytical design studies from the collected data, generating technical datasheets. As a final result, the database and technical datasheets were made available on a website, allowing to identify -mode office buildings. The published data provides a robust support to the development of thermal and energy performance analyses of such buildings.